Assimilation of Sea Surface Temperature data for Central Vietnam’s Water Using Regional Ocean Modeling System (ROMS) - Cuong, Nguyen Kim (VNU Journal of Science: Earth and Environmental Sciences, 2021)
This paper presents the preliminary results of SST data assimilation for the Central Vietnam’s water using Regional Ocean Modeling System (ROMS). ROMS was used to assimilate with high-resolution SST from satellite with 4D-PSAS assimilation technique. Multi-scale Ultra-high Resolution (Mur) SST dataset which combines satellite and microwave data was used. ROMS has been set up based on the HYCOM products with the forcing from ECMWF. The results showed that the HYCOM SST and MurSST has significant difference in temperature which could be up to 1 o C. Assimilated SST and hydrodynamic structures have been discussed. The impact of assimilation is mostly on the surface layer (less than 50 m). It’s possible to produce the best estimated initial fields with high resolution for the Central Vietnam water to further investigations.